The comprehensive complication index (CCI): proposal of a new reporting standard for complications in major urological surgery - Kowalewski, Karl-Friedrich; Müller, Dennis; Mühlbauer, Julia; Hendrie, Jonathan D.; Worst, Thomas; Wessels, Frederik; Walach, Margarete; Hardenberg, Jost von; Nuhn, Philipp; Honeck, Patrick; Michel, Maurice Stephan; Kriegmair, Maximilian (World journal of urology, 2021)
The comprehensive complication index (CCI) is a new tool for reporting the cumulative burden of postoperative complications on a continuous scale. This study validates the CCI for urological surgery and its benefits over the Clavien-Dindo-Classification (Clavien).